Pelatihan dan Simulasi Kesiapsiagaan Bencana Alam Pada Masyarakat di Kelurahan Pasie Nan Tigo, Kecamatan Koto Tangah, Kota Padang - Fitri Mailani; Elvi Oktarina; Dally Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Pasie Nan Tigo Koto Tengah Village, Padang City, is one of the villages that are included in the disaster-prone category, such as earthquakes, tsunamis, floods, abrasion, and storms. This service aims to provide training, education, and simulations related to natural disaster preparedness in Indonesia. Pasie Nan Tigo Village, Koto Tangah District. This activity was carried out by providing education, training, disaster mitigation simulations, preparation of disaster bags, basic life support (BHD), disaster victim evacuation techniques, and introduction to triage, splinting, and simple wound care. This activity was initiated by providing education and training for the community in RW 5, 11, and 12 for a week. The action began with giving a pre-test and ends with delivering a post-test. Furthermore, conducting simulations of earthquake preparedness in collaboration with local health centers, BASARNAS, BPBD, PMI, and local sub-districts. Qualitatively, the community said they were pleased to participate in this training and simulation; this could be seen from the community's enthusiasm for participating in the series of activities. One hundred sixty-six people participated in this activity. The knowledge of the community has been increased, and the training and simulations provided have provided a new learning experience for the community so that they are ready to be applied in dealing with a natural disaster. It is essential always to make efforts to increase community capacity in disaster prevention and management to reduce the number of victims or losses due to disasters. Therefore, it is necessary to have a straightforward program and adequate budget allocation from the Regional Government so that these activities can be carried out simultaneously and sustainably.